Pengaruh Metode Pembelajaran Problem Solving terhadap Keterampilan Berpikir Kreatif Materi Penyajian Data Kelas V - Pramesti, Rima; Iqbal Amrillah, Nur; Sutriyani, Wulan (Indonesian Journal of Islamic Elementary Education, 2023)
The lack of students' problem solving abilities and students' creative thinking skills is caused by several factors, including lack of precision in the selection and use of learning strategies and methods. The Problem Sloving Learning Method is considered suitable for training students in solving problems. The aim of this research is to determine the influence of the Problem Solving Method on mathematical creative thinking skills in class V data presentation material at SD N 03-04 Margoyoso and to determine the difference in the influence of mathematical creative thinking skills before and after applying the problem solving method to class data presentation material. V SD N 03-04 Margoyoso. This research uses a pre-experimental design method with a "one group pretest-posttest design" research design. The number of samples of students tested for this research was 19 people. The results of this research are that students' creative thinking skills were considered very low before using the Problem Solving learning method, which then resulted in an increase in students' creative thinking skills. It can be concluded that the use of problem solving learning methods in mathematics learning data presentation material influences the creative thinking skills of class V at SD N 03-04 Margoyoso.